The youth of antiquity: reception, homosexuality, alterity. (22nd August 2019) - Butler, Shane
Abstract: Classical reception studies and the Foucault-inflected study of ancient homosexuality came of age together, sharing several key dates in their core bibliographies. This article argues that this synchronicity is no coincidence. In particular, both endeavours have been driven by remarkably similar views of the 'otherness' of the past itself. Arguing that this view has partly been motivated by unspoken anxieties about scholarly agency, this article sheds some critical light on the presuppositions and methods of both subfields. It also aims to signpost some better, queerer ways forward, borrowed from the past itself.